Childhood antecedents of personality disorder: An alternative perspective - Widiger, Thomas A.; De Clercq, Barbara; De Fruyt, Filip (Development and psychopathology, 2009)
One of the fundamental limitations of the Diagnostic and Statistical Manual of Mental Disorders—Fourth Edition, Text Revision (DSM-IV-TR) categorical model of personality disorder classification has been the lack of a strong scientific foundation, including an understanding of childhood antecedents. The DSM-IV-TR personality disorders, however, do appear to be well understood as maladaptive variants of the domains and facets of the general personality structure as conceptualized within the five-factor model (FFM). Integrating the classification of personality disorder with the FFM brings to an understanding of the personality disorders a considerable body of scientific research on childhood antecedents. The temperaments and traits of childhood do appear to be antecedent to the FFM of adult personality structure, and these temperament and traits of childhood and adolescence are the likely antecedents for adult personality disorder, providing further support for the conceptualization of the adult personality disorders as maladaptive variants of the domains and facets of the FFM. Conceptualizing personality disorders in terms of the FFM thereby provides a basis for integrating the classification of abnormal and normal personality functioning across the life span.